Efficient fabrication of PLA/PBAT/ZnO films with inverted-pyramid Micro/nanostructures for robust anti-wet pack and antimicrobial protection - Yu Du; Rong Zhou; Kai Mu; Congyuan Zhang; Changjun Guo; Jiabao Lu; Zihao Li; Heng Xie; Ting Wu; Jinping Qu (Chemical Engineering Journal, 2026)

DASNet: A Convolutional Neural Network with SE Attention Mechanism for ccRCC Tumor Grading - Xiaoyi Yu; Donglin Zhu; Hongjie Guo; Changjun Zhou; Mohammed A. M. Elhassan; Mengzhen Wang (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Optimized dual-input dual-output TCN-BiLSTM deep learning network model based on Harris Hawk algorithm to predict ionospheric and gravity wave parameters of HFSWR during typhoon - Xuekun Chen; Hongjuan Yang; Changjun Yu (Advances in Space Research, 2025)

Mass spectrometry imaging unveils the fate of azithromycin in zebrafish: Uptake, distribution, transformation, and metabolic impact - Hang Fu; Leiyi Ji; Yanxiao Jiang; Changjun Yu; Hong Zhang; Guangfeng Kan; Jie Jiang (Journal of Environmental Chemical Engineering, 2025)

Digital footprints of wildlife crime: linking public search behavior to illegal trade dynamics for six keystone mammal taxa in China - Qingyong Ni; Yu Huang; Lei Xie; Mingwang Zhang; Yongfang Yao; Huailiang Xu; Changjun Zeng; Vincent Nijman; Meng Xie (Biological Conservation, 2025)

Deformation-resistant sponge-like hydrogel evaporators for efficient solar steam generation and high salinity desalination - Tingting Zhang; Jing Yang; Yifan Yang; Changjun Li; Xinghe Xu; Zhong-Zhen Yu; Xiaofeng Li (Desalination, 2025)

Preliminary analysis of landslides induced by the 3 April 2024 Mw 7.4 Hualien, Taiwan earthquake - Yi Chen; Chuang Song; Zhenhong Li; Bo Chen; Chen Yu; Jyr-Ching Hu; Xingmin Cai; Shuang Zhu; Qianwen Wang; Yixin Ma; Changjun Gu; Suju Li; et al. (Landslides, 2025)

From confrontation to co-production: How China's ENGOs facilitate residents' waste management systems - Shuang Tan; Yu Du; Changjun Li; Yu Gong; Yanqiang Du (Journal of Environmental Management, 2025)

Optimised CNN-LSTM-Attention deep learning network model based on RIME algorithm for predicting HFSWR gravity wave parameters during Typhoon Muifa (2022) - Xuekun Chen; Hongjuan Yang; Changjun Yu; Xuguang Yang (Advances in Space Research, 2025)

Preparation, purification and identification of antioxidant peptides from the placenta of Tibetan sheep - Haiwei Ren; Tianzhuo Qin; Qin Zhou; Lichao Pan; Changjun Yu; Yonggang Wang; Wenguang Fan; Zhizhong Li; Yi Zheng (Food Bioscience, 2025)

Bi2O2Se nanosheets coated with rosmarinic acid for colon-targeted treatment of inflammatory bowel disease - Jiahu Yao; Yang Yang; Hu Zhao; Chuanming Wang; Liang Jin; Tengyun Long; Wei Huang; Xiang Zhan; Xin Li; Xin Chen; Jinhu Xie; Bin Wu; et al. (Chemical Engineering Journal, 2025)

An investigation into the influence of solar flares and geomagnetic storms on the F2 layer of the ionosphere in Western Europe during March 2024 - Fangzhou Wu; Di Yao; Changjun Yu (Advances in Space Research, 2025)

Dynamic response of spherical tanks subjected to the explosion of hydrogen-blended natural gas - Li Mo; Ruichao Wang; Huai Yang; Yu Yang; Xia Wu; Wenlong Jia; Changjun Li; Chao Chen (Fuel, 2024)

Recombinant Marek’s disease virus type 1 provides full protection against H9N2 influenza A virus in chickens - Yuntong Chen; Qingqing Yu; Wenrui Fan; Xianying Zeng; Zibo Zhang; Guobin Tian; Changjun Liu; Hongmei Bao; Longbo Wu; Yanping Zhang; Yongzhen Liu; Suyan Wang; et al. (Veterinary Microbiology, 2024)

Surface patterned polyvinyl alcohol/CNT hydrogels for sustained solar powered high concentration brine desalination and salt harvesting - Changjun Li; Xiaoyang Fang; Chen Hu; Mang Zhao; Shumiao Li; Hao-Yu Zhao; Tingting Zhang; Zhong-Zhen Yu; Xiaofeng Li (Chemical Engineering Journal, 2024)

Dynamic responses of the floatover system with nonstationary mating processes: An experimental study - Xukai Fang; Xinchao Li; Rongze Wang; Yu Chen; Changjun Hu; Xiaoxian Guo; Wenyue Lu; Xin Li; Xinliang Tian (Ocean Engineering, 2024)

Rice rhizospheric effects and mechanism on soil cadmium bioavailability during silicon application - Yi Yang; Hua Peng; Kai Deng; Yu Shi; Wei Wei; Saihua Liu; Changjun Li; Jian Zhu; Yanjiao Dai; Min Song; Xionghui Ji (Science of The Total Environment, 2024)

Intelligent treatment of tannery wastewater via H2O2 photocatalytic oxidation coupled adsorption process - Huimin Yu; Miaomiao Tang; Jian He; Changjun Liu; Pan Wu; Wei Jiang (Journal of Water Process Engineering, 2024)

Combined Study of Gene Expression and Chromosome Three-Dimensional Structure in Escherichia coli During Growth Process - Hao Zhang; Changjun Shao; Jian Wang; Yanan Chu; Jingfa Xiao; Yu Kang; Zhewen Zhang (Current Microbiology, 2024)

Inhibiting advanced glycation end products (AGEs) of high-performance hemodialysis membranes self-assembled by gallic acid and Ti3C2Tx MXene - Qiqi Wang; Changjun Mu; Ya'nan Yu; Xia Feng; Yang He; Li Chen (Chemical Engineering Journal, 2024)

Nb2CTx MXene coating with inhibition of oxidative stress prepared by Marangoni effect for hemodialysis therapy - Yang He; Hanshu Sun; Yanjie Wang; Ya'nan Yu; Changjun Mu; Li Chen (Chemical Engineering Journal, 2024)

Untangling the critical success factors of the latest compulsory waste sorting initiative in Shanghai: The role of accountability governance - Shenghao Xie; Yu Gong; Abraham Zhang; Yanping Liu; Changjun Li (Journal of Cleaner Production, 2024)

Microseismic activity characteristics and range evaluation of hydraulic fracturing in coal seam - Yanan Qian; Quangui Li; Zhizhong Jiang; Qianting Hu; Wenbin Wu; Yu Liu; Liangwei Li; Zhichao Zhang; Changjun Yu; Wenxi Li (Gas Science and Engineering, 2024)

Evaluation of Hydraulic Fracturing in Coal Seam using Ground Microseismic Monitoring and Source Location - Yanan Qian; Quangui Li; Yunpei Liang; Qianting Hu; Wenxi Li; Jie Li; Changjun Yu; Ronghui Liu; Shuyue Peng (Rock Mechanics and Rock Engineering, 2024)

Real-time microseismic evaluation of coalbed methane reservoir stimulation based on improved metaheuristic inversion strategy - Wenxi Li; Quangui Li; Qianting Hu; Yanan Qian; Huiming Yang; Zhizhong Jiang; Changjun Yu (Gas Science and Engineering, 2023)

Field-friendly and ultra-fast detection platform without nucleic acid extraction for virus detection - Gaihua Cao; Yifan Xiong; Yue Qiu; Jun Yang; Yu Wang; Fuping Nie; Danqun Huo; Changjun Hou (Analytica Chimica Acta, 2023)

Barriers to compulsory waste sorting for a circular economy in China - Abraham Zhang; Shenghao Xie; Yu Gong; Changjun Li; Yanping Liu (Journal of Environmental Management, 2023)

Phenamacril and carbendazim regulate trichothecene mycotoxin synthesis by affecting ROS levels in F. asiaticum - Yu Zhang; Fuyu Zhang; Wenyong Shao; Wenchan Chen; Zhihui Zhang; Dongya Shi; Changjun Chen (Pesticide Biochemistry and Physiology, 2023)

Multiple accurate and sensitive arrays for Capripoxvirus (CaPV) differentiation - Gaihua Cao; Yifan Xiong; Meimei Shi; Yue Qiu; Yu Wang; Fuping Nie; Danqun Huo; Changjun Hou (Analytica Chimica Acta, 2023)

Risk of plant invasions and management planning in the Tibetan Plateau, China - Bo Wei; Yili Zhang; Linshan Liu; Changjun Gu; Zhaofeng Wang; Haibin Yu; Bohao Cui; Dianqing Gong (Journal of Biogeography, 2023)
Aims Mountain environments have high biodiversity and face an accelerating plant invasion risk. Given the enormous ecological and economic value of these ecosystems, there is an urgent need to detect and rapidly respond to invasive species risk. Here, the Tibetan Plateau (TP) in China was selected to examine distribution patterns of invasive alien plants (IAPs) and propose management strategies. Location The Tibetan Plateau in China. Methods Based on native and non‐native occurrences of 123 IAPs alongside environmental variables, we assembled species distribution models and the MIGCLIM model to simulate suitable growth and dispersal areas under current climatic conditions. All IAPs were classified based on the predicted suitable area size, occurrence number and harm level to propose various management strategies. Results There was a significant separation between the climate niches of most IAPs and the climatic conditions of the TP, meaning the areas suitable for most IAPs were limited to low latitudes and elevations. These areas also have further dispersal risks and risks for new IAPs being introduced. Among 123 IAPs, 23 species had above‐average occurrences and suitable distribution areas; in the remaining 100 occurrences and distributions, at least one IAP was less than the average. Main Conclusions Suitable areas for IAPs in the TP are currently limited to low‐elevation regions, which are also at a higher risk of further expansion. Management measures should focus on potential high‐risk areas and diffusion pathways where IAPs can spread further. Efforts should prevent species that have not been established but have large potential suitable areas from being introduced, eradicate established IAPs with limited suitable areas, and control established IAPs. These results can provide a reference for developing more efficient and cost‐effective management strategies.

Salt-resistant wood-based solar steam generator with top-down water supply for high-yield and long-term desalination of seawater and brine water - Chen Hu; Wei Li; Hao-Yu Zhao; Changjun Li; Zai-Yuan Ma; Longyun Hao; Yaokun Pang; Zhong-Zhen Yu; Xiaofeng Li (Chemical Engineering Journal, 2023)

Alleviation of Cd-polluted paddy soils through Si fertilizer application and its effects on the soil microbial community - Hua Peng; Kai Deng; Yu Shi; Saihua Liu; Zhu Jian; Changjun Li; Xionghui Ji; Shengnan Li (Science of The Total Environment, 2023)

Reduction of miR-133a-3p contributes to apoptosis and gasdermin E-mediated pyroptosis of keratinocytes in skin exposed to ultraviolet B radiation - Changjun Song; Wenlan Zhang; Ta Xiao; Min Li; Yiqun Zhang; Xuecui Wei; Yujie Chen; Ni Lian; Yangying Ke; Hui Yu; Min Li; Heng Gu; et al. (Journal of Photochemistry and Photobiology B: Biology, 2023)

Changes in the m6A RNA methylome accompany the promotion of soybean root growth by rhizobia under cadmium stress - Xue Han; Jialin Wang; Yu Zhang; Youlin Kong; Huiying Dong; Xuezhen Feng; Tianshu Li; Changjun Zhou; Jidong Yu; Dawei Xin; Qingshan Chen; Zhaoming Qi (Journal of Hazardous Materials, 2023)

circ_0044516 functions in the progression of gastric cancer by modulating MicroRNA-149-5p/HuR axis - Yang Yang; Baoping Cai; Xinxin Shi; Chen Duan; Tong Tong; Changjun Yu (Molecular and Cellular Biochemistry, 2022)

Clinical characteristics of re-hospitalized COVID-19 patients with recurrent positive SARS-CoV-2 RNA: a retrospective study - Lei Pan; Runsheng Wang; Na Yu; Chao Hu; Junhong Yan; Xiaomin Zhang; Tao Wang; Jungui Hao; Fuquan Gao; Tonggang Liu; Jing Wang; Xiaojing Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

The bacterial RNA ligase RtcB accelerates the repair process of fragmented rRNA upon releasing the antibiotic stress - Muhammad Ramzan Manwar; Changjun Shao; Xing Shi; Jian Wang; Qiang Lin; Yigang Tong; Yu Kang; Jun Yu (Science China Life Sciences, 2020)

Co-circulation of multiple genotypes of influenza A (H7N9) viruses in eastern China, 2016-2017 - Xian Qi; Xiaofei An; Yongjun Jiao; Huiyan Yu; Ke Xu; Lunbiao Cui; Shenjiao Wang; Fei Deng; Xiang Huo; Haodi Huang; Qigang Dai; Changjun Bao (Archives of Virology, 2018)

Ground Deformation Monitoring in Tongzhou Based on High Resolution SAR Images - Changjun Huang; Jiming Guo; Xiaodong Yu; Zhiping Nie (Journal of the Indian Society of Remote Sensing, 2016)

Baseline sensitivity of natural populations and characterization of resistant strains of Botrytis cinerea to fluazinam - Wenyong Shao; Weichao Ren; Yu Zhang; Yiping Hou; Yabing Duan; Jianxin Wang; Mingguo Zhou; Changjun Chen (Australasian Plant Pathology, 2015)

PEGylated Multi-Walled Carbon Nanotubes for Encapsulation and Sustained Release of Oxaliplatin - Linlin Wu; Changjun Man; Hong Wang; Xiaohe Lu; Qinghai Ma; Yu Cai; Wanshan Ma (Pharmaceutical Research, 2013)

Sensitivity ofFusarium graminearum to fungicide JS399-19:In vitro determination of baseline sensitivity and the risk of developing fungicide resistance - Yu Chen; Hengkui Li; Changjun Chen; Mingguo Zhou (Phytoparasitica, 2008)